The Effects of Parental Behavior on Infants' Neural Processing of Emotion Expressions. Issue 3 (11th February 2015) - Taylor‐Colls, Samantha; Pasco Fearon, R. M.
<x xml:space="preserve">Abstract</x> Infants become sensitive to emotion expressions early in the 1st year and such sensitivity is likely crucial for social development and adaptation. Social interactions with primary caregivers may play a key role in the development of this complex ability. This study aimed to investigate how variations in parenting behavior affect infants' neural responses to emotional faces. Event‐related potentials (ERPs) to emotional faces were recorded from 40 healthy 7‐month‐old infants (24 males). Parental behavior was assessed and coded using the Emotional Availability Scales during free‐play interaction. Sensitive parenting was associated with increased amplitudes to positive facial expressions on the face‐sensitive ERP component, the negative central. Findings are discussed in relation to the interactive mechanisms influencing how infants neurally encode positive emotions.